(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2013)
Financial Sector Reforms set in motion in 1991 havegreatly changed the face of Indian Banking. The banking industry has moved gradually from a regulatedenvironment to a deregulated market economy. The market developments kindled byliberalization and globalization have resulted in changes in the intermediationrole of banks. The pace of transformation has been more significant in recenttimes with technology acting as a catalyst. While the banking system has donefairly well in adjusting to the new market dynamics, greater challenges lieahead. Financial sector would be opened up for greater internationalcompetition under WTO.